FACTORS RELATED TO INCIDENCE OF MALNUTRITION IN UNDER FIVE CHILDREN - Okta, Jaa Oktafa Once; Mustafa , Annasari; Yudianti, Ika (UNIVERSITAS AIRLANGGA, 2024)
Background: Malnutrition is one of the main nutritional problems in Indonesia and East Java. Malnutrition is the cause of more than 1/3 of 9.2 million deaths in children under the age of 5 in the world. Toddlers are a very vulnerable group related to nutrition in society. If the nutrition of children under five is not fulfilled continuously it will cause stunting. Method: This study uses descriptive analysis to overview of the problem of factors related to the incidence of undernutrition in children under five at Posyandu Randugading, Tajinan District, Malang Regency. The sample consisted of 36 children under five using a total sampling technique. This data was obtained from the nutritional status report of the Tajinan Community Health Center which met the nutritional criteria of less than -3 SD to <-2 SD based on the z-score formula. This research instrument used a questionnaire, data collection was carried out by interviews to obtain data on variables Frequency of giving MP-ASI, Infectious diseases, Exclusive breastfeeding, Mother's weight gain during pregnancy, and Number of siblings. The data collection period was carried out on 18 April 2023–25 April 2023. Result: from 36 children showed that 30.55% giving MP-ASI at most was according to the child's request, children who have had history of an infectious disease 58.33%, exclusive breastfeeding was 50 %, weight gain during pregnancy less as it shouls was 50%, children who have siblirng is more than 2 was 63.89%. Conclusion: Malnutrition children under five year old in Posyandu Randugading, Tajinan District, Malang Regency have characteristic related to feeding meals was most of them according to the child's request, majority children have history of an infectious disease, Mother wight gain during pregnancy lower as it should, majority children have more than 2 sibling.